POPULASI LALAT BUAH (Bactrocera spp.) DAN PARASITOIDNYA PADA PERTANAMAN CABAI DI BANJARNEGARA - Eko Apriliyanto; Bondan Hary Setiawan (Jurnal Ilmiah Media Agrosains, 2016)
The aims of this study is to know the fruitfly and parasitoid populations in chili cropping in Banjarnegara. The study was conducted on April to October 2014. The fruitflies sampling was conducted by using fruitflies host maintenance. It means that collect the chilies wich has indicated attaced by fruitflies. One experimental unit was 10 pieces of chilies placed in a plastic jar filled with steril sand and covered with guaze. Further more, chilies left until the imago appearance, so that the fruitflies and parasitoid could be identified and could be accounted. The research was held in laboratory using a completely randomized block design with three experimens and nine repetitions, so there were 27 experimental units. Experimen consist of three sampling location wich attacked by chili fruitflies (Purwanegara, Karangkobar and Pagentan). The decision of certain location research used purposive sampling technique. Data analysis used F test, if there was significant different followed by Duncan’s Multiple Range Test at 5% level. The highest population of Bactrocera spp. in Pagentan is 20.78 individuals, while in district Purwanegara and Karangkobar are 2.11 and 1.67 individuals. Family Braconidae parasitoid population have not been able to reduce fruitfly population. Parasitoid population in distric Purwanegara, Karangkobar and Pagentan are 0.44, 0.22, and 1.22 individuals.